The Impact of the Digital Divide on Equal Employment Opportunities in the Digital Economy Era - Deva Dwi Prasetyo; Defazel Mirza Kafi khaeruddin; Antonius Mouritzh Aso; Agnesito Prosperity; Humairo Humairo (Journal of Digital Law and Policy, 2026)
The rapid growth of the digital economy has transformed labor markets and created new employment opportunities through digital platforms, remote work, and technology-driven entrepreneurship. However, unequal access to digital infrastructure, internet connectivity, and digital literacy continues to limit participation in these opportunities, particularly among individuals residing in rural and underdeveloped regions. This study examines the impact of the digital divide on equal employment opportunities in Indonesia’s digital economy and analyzes the issue through the perspective of Pancasila, particularly the Fifth Principle of “Social Justice for All Indonesian People.” A qualitative research approach was employed using a Systematic Literature Review (SLR) and policy analysis of scholarly publications, government reports, and official documents published between 2020 and 2025. The collected data were analyzed using thematic content analysis to identify key challenges and opportunities related to digital inclusion and employment participation. The findings indicate that disparities in digital infrastructure, digital literacy, platform accessibility, and governance continue to contribute to employment inequality within the digital economy. At the same time, digital transformation provides significant opportunities for entrepreneurship, remote work, digital education, and workforce development. Based on these findings, this study proposes a Pancasila-Based Digital Inclusion Framework consisting of four pillars: Inclusive Digital Infrastructure, Digital Literacy and Human Capital Development, Inclusive Governance and Regulatory Support, and Ethical Human-Centered Technology. The study concludes that aligning digital transformation with the principles of social justice is essential to ensuring equal employment opportunities and promoting inclusive and sustainable development in Indonesia’s digital economy